South Africa : studies on the social dimensions of globalization - Hayter, Susan (ILO GenevaCH, 2001)
Contains a brief description of the process of economic liberalization and tracks the key labour and social developments that are taking place. Attempts to determine the links between trade and the country's poor employment performance, taking the years from 1994 to 1997 as the main period of analysis. Assesses the policies and conditions that will be necessary to consolidate the potential gains from globalization, and at the same time make the process socially sustainable.